ChemInform Abstract: Hypervalent Iodine as a Terminal Oxidant in Wacker‐Type Oxidation of Terminal Olefins to Methyl Ketones. Issue 30 (7th July 2016) - Chaudhari, Dipali A.; Fernandes, Rodney A.
Abstract: A Markovnikov‐selective oxidation of terminal olefins by a combination of palladium(II) acetate and Dess—Martin periodinane is described.